2013
DOI: 10.20886/jphh.2013.31.3.221-227
|View full text |Cite
|
Sign up to set email alerts
|

Teknik Penyadapan Pinus Untuk Peningkatan Produksi Melalui Stimulan Hayati

Abstract: The increased demand of pine resin both for domestic and overseas markets has necessitated efforts to enhance pine-sap production. The use of strong acid-based conventional stimulants has been long employed by Perum Perhutani, but questions arise regarding the environment effect as well as growth survival of the tapped pine trees. Consequently, the use of biostimulant deserves thorough consideration, since not only will assure friendly-environmental effects but also securing the sustainability of the pine tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The limited effect of ETRAT on oleoresin induction in the present experiments may have been related to the weak acidic nature of citric acid compared to sulfuric acid in maintaining resin flow. This result is consistent with the research described by Sukadaryati and Dulsalam (2013), who found the increase of oleoresin production by various biostimulants, but the values were still lower than those of CAS stimulant. Sukadaryati et al (2014) showed that various weak acidic biostimulants did not produce resin as much as sulfuric acid in P. merkusii tapping.…”
Section: The Interaction Between Of Stimulants and Sitessupporting
confidence: 93%
See 1 more Smart Citation
“…The limited effect of ETRAT on oleoresin induction in the present experiments may have been related to the weak acidic nature of citric acid compared to sulfuric acid in maintaining resin flow. This result is consistent with the research described by Sukadaryati and Dulsalam (2013), who found the increase of oleoresin production by various biostimulants, but the values were still lower than those of CAS stimulant. Sukadaryati et al (2014) showed that various weak acidic biostimulants did not produce resin as much as sulfuric acid in P. merkusii tapping.…”
Section: The Interaction Between Of Stimulants and Sitessupporting
confidence: 93%
“…Unfortunately, those stimulants did not work satisfactorily and were applied only in certain stands (Sukadaryati et al 2014;Darmastuti et al 2016;Lempang 2017). Natural or biostimulant agents were also tried in a P. merkusii stand from Perhutani site (Sukadaryati and Dulsalam 2013). Furthermore, local people employed by Perhutani also used aqueous sulphuric acid in a high concentration to increase oleo-resin yield, which could cause deleterious effects during the economic life of pine trees.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Some studies have been conducted to explore the effect of stimulants on oleoresin yield of Pinus merkusii trees. [7][8][9][10] However, the study regarding the effect of site and tapping period remains limited. Besides site and stimulant factors, tree characteristics have been reported to be related to the resin yield.…”
Section: Introductionmentioning
confidence: 99%